GPs’ experienced challenges and strategies for supporting patient self-management in disease management programs for type 2 diabetes mellitus and coronary heart disease: a qualitative study - Pilic, Larisa; Molkentin, Kira; Herrmann, Alina; Redaèlli, Marcus; Kupsch, Lisa; Lehmann, Lion; Bödecker, August-Wilhelm; Müller, Beate Sigrid; Stock, Stephanie; Wilm, Stefan (BMC primary care, 2025)
Effective self-management (SM) is essential for improving health and preventing severe complications in patients with lifestyle-related chronic conditions, such as type 2 diabetes mellitus (T2DM) and coronary heart disease (CHD). Thus, enhancing patients’ SM through self-management support has become an integral part of chronic care programs worldwide. However, information on the current focus on SM in German disease management programs (DMPs) is very limited. The aim of this study was to understand general practitioners’ (GPs’) experiences and strategies for promoting SM.
Gesehen am 03.12.2025